Heterometathesis of diphosphanes (R2P–PR2) with dichalcogenides (R′E–ER′, E = O, S, Se, Te). Issue 22 (31st May 2022) - Branfoot, Callum; Pringle, Paul G.; Pridmore, Natalie E.; Young, Tom A.; Wass, Duncan F.
Abstract : The reactions of R2 P–PR2 with R′E–ER′ (where E = Se, S, O, Te) to give R2 P–ER′ have been explored experimentally and computationally. 31 P NMR evidence suggests that Mo(0) complexes of Ph2 P–SePh feature P- and Se- linkage isomers. Abstract : The reactions of R2 P–PR2 with R′E–ER′, (where E = Se, S, O, Te) to give R2 P–ER′ have been explored experimentally and computationally. The reaction of Ph2 P–PPh2 with PhSe–SePh gives Ph2 P–SePh (1 ) rapidly and quantitatively. The P–P/Se–Se reaction is inhibited by the addition of the radical scavenger TEMPO which is consistent with a radical mechanism for the heterometathesis reaction. Compound 1 has been fully characterised, including by X-ray crystallography. A range of other Ar2 P–SeR (R = Ph, n Bu or CH2 CH2 CO2 H) have also been prepared and characterised. The reaction of 1 with [Mo(CO)4 (nbd)] (nbd = norbornadiene) gives two products which, from their characteristic 31 P NMR data, have been identified as cis -[Mo(CO)4 (Ph2 PSePh– P )2 ] (8 ) and the mixed-donor complex cis -[Mo(CO)4 (Ph2 P–SePh– P )(Ph2 P–SePh– Se )] (9 ). It is deduced that the P and Se atoms in ligand 1 have comparable capacity to coordinate to Mo(0). The reaction of Ph2 P–PPh2 with PhS–SPh gives Ph2 P–SPh (2 ) quantitatively but no reaction was observed between Ph2 P–PPh2 and PhTe–TePh. Heterometathesis between Ph2 P–PPh2 and t BuO–O t Bu does not occur thermally but has been observed under UV irradiation to give Ph2 P–O t Bu along with P(v ) oxidation by-products. DFT calculations have been carried out to illuminate why heterometatheses with dichalcogenides R′E–ER′ occur readily when E = S and Se but not when E = O and Te. The calculations show that heterometathesis is predicted to be thermodynamically favourable for E = O, S and Se and unfavourable for E = Te. The fact that a metathesis reaction between Ph2 P–PPh2 with t BuO–O t Bu is not observed in the absence of UV radiation, is therefore due to kinetics.